2005
DOI: 10.1002/app.22095
|View full text |Cite
|
Sign up to set email alerts
|

Water absorption mechanism and some anomalous effects on the mechanical and viscoelastic behavior of an epoxy system

Abstract: During the past decades there has been a great accumulation of important data on the diffusion of water molecules in polymeric solids and its effect on the mechanical and viscoelastic behavior of polymers. It has become apparent that in many cases diffusion in polymers as well as its effect exhibits features that cannot be expected from classical theories and that such departures are related to the molecular structure characteristics of polymers. In the present investigation, the mechanical and viscoelastic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 17 publications
6
70
1
1
Order By: Relevance
“…The amount of free volume is considered as the main driving force to water absorption, and is related to several different physical characteristics of the polymer [15,16,[28][29][30][31] . These physical characteristics are intimately linked to the degree of cure, the stoichiometric ratio and with the stiffness of the molecular bonds [29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of free volume is considered as the main driving force to water absorption, and is related to several different physical characteristics of the polymer [15,16,[28][29][30][31] . These physical characteristics are intimately linked to the degree of cure, the stoichiometric ratio and with the stiffness of the molecular bonds [29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
“…Several authors consider that the Fickian model is not able to describe the complete water absorption behavior of several polymers and/or polymer composites [14][15][16][17] . In fact, in many instances it was found that the Fickian behavior can fit the experimental data points only at the early stages of the absorption process, failing, however, to describe the behavior when the absorption time increases.…”
Section: Non-fickian Behaviormentioning
confidence: 99%
“…The obtained values of the main and sub-T g temperature for the case of 0.05% CNT content are displayed in Figure 5. This extra relaxation peak is attributed to the bound water molecules either acting as a plasticizer or participating in the network via hydrogen bonding [14,23]. Thus, by affecting the inter-and intra-molecular flexibility of the backbone it introduces a new relaxation mechanism.…”
Section: Dgeba/teta/mwcnt Water Saturated Compositesmentioning
confidence: 99%
“…In particular, the curing conditions of the nanocomposites and their results are different from those of the pure epoxy probably due to the effect of the nanoparticles on the crosslinking mechanism [8]. With regard to the thermoset epoxies a significant amount of data has been accumulated about water absorption and diffusion and their effect on the dynamic mechanical behaviour [11,14]. However, for the understanding and explanation of all the experimental data there are still some points open to question.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant concern throughout the service life of the polymer composite radome is its tendency to absorb moisture [2]. Assessment of the deleterious effects of moisture ingress on the mechanical properties of fiber-reinforced composites has garnered much focus throughout several decades of research [3][4][5][6][7]. In contrast, quantifying and assessing dielectric property degradation as a result of absorbed moisture has not received equivalent attention, though some studies have been performed [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%